Drupal For Dummies - Beighley, Lynn (John Wiley & Sons, 2011)
Learn to set up, manage, and administer a Drupal web siteDrupal offers unparalleled flexibility for content-managed web sites, and Drupal 7 is the easiest version to use yet. This new edition teaches you the fast, fun, and easy way to get started with Drupal. Even if you have no Drupal experience, you'll quickly learn how to download and install Drupal, set up your first content-managed site, apply templates, use modules, and more. Drupal gurus Lynn Beighley and Seamus Bellamy show you how to take advantage of what Drupal has to offer, make the most of the new features in Drupal 7, and demysti.
Site Map Module. - Includes bibliographical references and index. - Print version record
Keywords: Drupal (Computer file); Web sites -- Authoring programs; Web site development; Sites Web; Systèmes-auteur; Sites Web; Développement; COMPUTERS; Web; Web Programming; Web sites; Authoring programs